If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 2m Solving 15 = 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 15 + -2m = 2m + -2m Combine like terms: 2m + -2m = 0 15 + -2m = 0 Add '-15' to each side of the equation. 15 + -15 + -2m = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -2m = 0 + -15 -2m = 0 + -15 Combine like terms: 0 + -15 = -15 -2m = -15 Divide each side by '-2'. m = 7.5 Simplifying m = 7.5
| -5+x=7 | | -2+5=19 | | 32x^4-4x^2-1=0 | | x-(-10)=-14 | | -10(12-a)=4(a+3) | | 4x+673(45)=37 | | x+(-8)=-12 | | -8+4b=-8(-4b-6) | | 70=(61+71+70+x)/4 | | 70=(61+71+70+x)/2 | | r(z^8+2)+(z^8+2)=0 | | -7+5v=-5(v-5)+6v | | 6+x=-8 | | 5x+17x=110 | | 5x^2-5x+15=0 | | -m^2+23m-42=0 | | -2m+2m=-2m-4 | | 5x-22=-28 | | 1.5x+12=18 | | -2r-5=7+r | | x^2+4x=165 | | 7x^2-5x-12=0 | | -63.75=12.5k | | 8x-12+8x-32=4x+12 | | x^2+x-37=0 | | 1.4q-1.8-4.5q=-2.1q-1.8 | | 25+6t= | | 8x+12+8x-32=4x+12 | | -12x+9=-6 | | -3m=25 | | 0.6(7x+14)=1.2-(x+2) | | 2x+2x=-3 |